Use of bank assets in financing the expanded reproduction of Russian economy - Zubareva, L.V.; Orlova, N.L.; Safronova, Yu.V (Opción, 2019)
The article draws attention to the use of bank assets in Russian reproduction via statistical analysis of proportions and qualitative comparative analysis. As a result, there is a significant limitation of real participation of the banking sector in the financing of expanded reproduction, which is associated with a fairly high level of capital concentration in the largest banks that are controlled, usually by the state. In conclusion, the contradictions of banking assets consolidation are reduced due to an improved monitoring of limited financial resources efficiency which will result in an increased investment in the real sector of the economy.